2013
DOI: 10.1063/1.4793611
|View full text |Cite
|
Sign up to set email alerts
|

Ferrofluid droplet heating and vaporization under very large magnetic power: A thermal boundary layer model

Abstract: In this work, heating and vaporization of a liquid droplet with dispersed magnetic nanoparticles (ferrofluid) are analyzed. The ferrofluid droplet is in a quiescent inert gas phase with a temperature which is set down equal to, higher and lower than the liquid boiling temperature. Under these conditions, an alternating magnetic field is applied and, as a result, the magnetic nanoparticles generate heat by the Brownian relaxation mechanism. In this mechanism, the magnetic dipoles present a random orientation du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…When alternating magnetic field is applied magnetic particles in a ferrofluid can be heated by magneto relaxation heating [41]. It was also shown that vaporization rate is higher when alternating field is applied [41]. In the present case we have applied uniform magnetic field hence rotation of particles which is largely responsible to produce thermal diffusion in the fluid does not occur.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…When alternating magnetic field is applied magnetic particles in a ferrofluid can be heated by magneto relaxation heating [41]. It was also shown that vaporization rate is higher when alternating field is applied [41]. In the present case we have applied uniform magnetic field hence rotation of particles which is largely responsible to produce thermal diffusion in the fluid does not occur.…”
Section: Discussionmentioning
confidence: 75%
“…It can be determined by measuring weight loss at different time intervals [40]. When alternating magnetic field is applied magnetic particles in a ferrofluid can be heated by magneto relaxation heating [41]. It was also shown that vaporization rate is higher when alternating field is applied [41].…”
Section: Discussionmentioning
confidence: 99%
“…A PFPE based ferro uid was prepared and characterized by Black et al [15] , which was found to have low volatility under high temperature.Li et al [16] calculated the evaporation rate of hydrocarbon based and uorocarbon based ferro uid under four different vacuum levels. Cristaldo et al [17][18][19] numerically analyzed heating process of ferro uid droplet under an alternating magnetic eld with a thermal boundary layer model. Bolotov et al derived equations of evaporation rate to estimate the life of a tribounit with ferro uid in the ambience of a vacuum [20] and a gas [21] .…”
Section: Introductionmentioning
confidence: 99%
“…When magnetic nanoparticles are embedded in these droplets, it is possible to accelerate those processes allowing the construction of more compact chambers. [12][13][14] Ferrofluids contain magnetic particles whose mobility can be controlled by a magnetic field. Regarding the applications in MH, the interest is the absorption of large amounts of energy when the magnetization of the particles is reversed.…”
Section: Introductionmentioning
confidence: 99%
“…This way, the magnetic field modifies the temperature profile in such a way that the boiling condition is found inside the droplet, which can be interpreted as bubble formation and droplet rupture. 13,14 This way, magnetic hyperthermia may be used as an extra atomization process to control the size of droplets and, accordingly, the vaporization rate of sprays.…”
Section: Introductionmentioning
confidence: 99%